2016
DOI: 10.1007/s10792-016-0264-x
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of central corneal thickness and endothelial parameters with three different non-contact specular microscopy devices

Abstract: We aimed to compare the measurements of central corneal thickness (CCT) and endothelial parameters with three different non-contact specular microscopy (SM) devices. Fifteen eyes of 15 healthy individuals (6 males; 9 females) were enrolled in the study. Mean age was 37.93 ± 15.13 years. Endothelial parameters and CCT were measured with Nidek CEM-530, Topcon SP-3000P, and Tomey EM-3000 SM devices by the same physician. Endothelial parameters included endothelial cell count (ECC), maximum, minimum, and average e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Our results yielded an acceptable ECD loss due to surgical trauma, but some cases show unreal gains (and drops) in ECD as the result of measurement error. The reliability of EC analysis is a well-discussed topic [26][27][28][29] with count errors of up to 9% with the SP2000P [29]. In addition, in our study, both the Topcon SP-2000P as the SP-3000P specular microscope was used during follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…Our results yielded an acceptable ECD loss due to surgical trauma, but some cases show unreal gains (and drops) in ECD as the result of measurement error. The reliability of EC analysis is a well-discussed topic [26][27][28][29] with count errors of up to 9% with the SP2000P [29]. In addition, in our study, both the Topcon SP-2000P as the SP-3000P specular microscope was used during follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…The correct explanation could be that the Nidek SM device tends to give thicker CT measurements than other SM devices. In fact, Cakici et al 24 found that the mean CT value provided by the Nidek SM was thicker than that provided by the Tomey SM (Nagoya, Japan) and Topcon SM devices.…”
Section: Discussionmentioning
confidence: 97%
“…We compared the Oculus Pentacam HR and the Nidek CEM-530 SM because these two devices do not require corneal contact and because both the Pentacam 11,15,[18][19][20][21][22] and Nidek 23,24 have been singularly compared with other devices. Among these comparisons, only a few have involved a Scheimpflug camera versus SM devices 15,[18][19][20] and only one has involved a Scheimpflug camera versus the Nidek CEM-530.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors describe that different types of CSMs, manufactured by different companies, are not interchangeable. [3][4][5][6][7][8]16 During our clinical practice and research, we also encountered an interchangeability problem when using different CSMs. In our research involving longitudinal ECC analysis after Artisan IF-pIOLs, we discovered a significant difference in ECCs when we replaced our "old" SP-2000P CMS with the newer SP-3000P version; see Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Different CSMs and image analysis methods have been evaluated for comparability and are usually not interchangeable. [3][4][5][6][7][8] To be able to reliably compare longitudinal ECC measurements, it is therefore wise to use the same CSM and analysis system for all measurements. However, when instruments wear out, it is often no longer possible or even desirable to replace it with the same previous type.…”
Section: Introductionmentioning
confidence: 99%